Lucha en las calles - Scarrow, Simon (Scarrow, Simon. Gladiator., 2015)
Now a member of Julius Caesar's palace. Marcus's gladiator training continues at an elite school in Rome. But the city streets are plagued by vicious gang-war attacks, and Caesar must employ his own gang leader, who learns of a plot to murder him. Only Marcus can go in undercover. But he's in terrible danger. If the rival gang discovers him, the price will be fatal. Julius Caesar's isn't the only life at risk.